1992
DOI: 10.1146/annurev.iy.10.040192.002321
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Variations: Observations on Suppressor T Cells and Leprosy

Abstract: Few areas of immunology have been so controversial as that of suppressor T cells. Studies of T cell clones derived from patients with infectious diseases, including leprosy, and allergies have allowed the delineation of functional human T cell subsets. Both CD4 and CD8 cells can be discriminated into subsets that are differentiated by their functions and patterns of lymphokines. Type 1 CD4 cells reactive with lepromin and PPD produce IFN-gamma and IL-2 predominantly, while Type 2 CD4 clones, specific for tetan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(56 citation statements)
references
References 60 publications
3
50
0
Order By: Relevance
“…Furthermore, unusual restriction of CD8+ T cells through MHC class I1 cannot be discounted. This has been reported with HLA-DQ and antigen-specific, suppressive CD8+ T cells from patients with lepromatous leprosy (39). Because of the preponderance of DR1/4 in RA patients, only a larger study with appropriately chosen, HLA-matched, and agematched controls would define this.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, unusual restriction of CD8+ T cells through MHC class I1 cannot be discounted. This has been reported with HLA-DQ and antigen-specific, suppressive CD8+ T cells from patients with lepromatous leprosy (39). Because of the preponderance of DR1/4 in RA patients, only a larger study with appropriately chosen, HLA-matched, and agematched controls would define this.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, CD8 autoreactive T cells may act either as pathogenic T cells (Bloom et al, 1992, Jiang et al, 1992, Rifa'i et al, 2004, Sun et al, 1988b, Sun et al, 1999a or suppressive T cells, which inhibit disease development (Endharti et al, 2005, Rifa'i et al, 2004. In the present study, we studied the role of the CD8 + CD45RC low T cell subset in the pathogenesis of the autoimmune diseases, EAE and EAU.…”
Section: Discussionmentioning
confidence: 94%
“…Although many studies have shown that CD8 + T cells play important roles in the pathogenesis of autoimmune diseases (Bloom et al, 1992, Jiang et al, 1992, Rifa'i et al, 2004, Sun et al, 1988b, Sun et al, 1999a, Endharti et al, 2005, the cellular and molecular mechanisms involved remain largely unclear. Moreover, CD8 autoreactive T cells may act either as pathogenic T cells (Bloom et al, 1992, Jiang et al, 1992, Rifa'i et al, 2004, Sun et al, 1988b, Sun et al, 1999a or suppressive T cells, which inhibit disease development (Endharti et al, 2005, Rifa'i et al, 2004.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacillus Calmette-Guérin's inadequacy as TB vaccine may, similarly, at least in part (10), be accounted for by its ability to induce Tregs (11). Tregs have been isolated from leprosy patients (12,13), which suppressed CD4 ϩ Th1 cells (12)(13)(14). More recently, IL-10-producing T cells were reported in anergic TB patients (15), and increased frequencies of CD4 ϩ CD25 HI T cells have been found in the circulation of TB patients (16,17).…”
Section: R Egulatory T Cells (Tregs) Play An Important Role In Maintamentioning
confidence: 99%